Multidetector computed tomography diagnosis of small bowel intussusceptions in adults: observations in a 10-year single-center study. (December 2021) - Hu, Maoqing; Long, Fang; Long, Wansheng; Jin, Zhifa; Yin, Hekun; Li, Chao
Background: The etiologies of small bowel intussusception (SBI) in adults are varied. Purpose: To investigate multidetector computed tomography (MDCT) characteristics in adults with neoplastic and non-neoplastic SBI. Material and Methods: Clinical data and MDCT images diagnosed with SBI in adults from January 2010 to May 2020 were retrospectively reviewed. Results: The study included a total of 71 patients. Forty-two patients had a combined total of 55 neoplastic intussusceptions, including 29 patients with benign tumors and 13 patients with malignant tumors. Twenty-nine patients had a combined total of 36 non-neoplastic intussusceptions, of which the condition was idiopathic in 23 patients and cased by non-neoplastic benign lesions in six patients. There were no significant differences in patient age or sex ratio in the neoplastic and non-neoplastic groups. In the non-neoplastic group the intussusceptions were shorter in length (3.6 cm vs. 13.2 cm, P <0.05) and smaller in transverse diameter (2.8 cm vs. 4.2 cm, P <0.05), and less likely to be associated with intestinal obstruction (2 vs. 18, P <0.05). The percentage of patients with multiple intussusceptions was greater in the neoplastic group (10/42, 23.8% vs. 4/29, 13.8%). In the non-neoplastic group only one lead point was detected (in a patient with Meckel's diverticulum), whereas lead points were detected in all 55 intussusceptions in the neoplastic group. Conclusion: There are differences in the clinical and MDCT manifestations of adult neoplastic and non-neoplastic SBIs. Whether a lead point is present or not has implications with regard to deciding on the most appropriate treatment and avoiding unnecessary surgery.